Association of periprocedural intravenous morphine use on clinical outcomes in ST‐elevation myocardial infarction (STEMI) treated by primary percutaneous coronary intervention: Systematic review and meta‐analysis. Issue 1 (26th October 2019) - Batchelor, Riley; Liu, David Hongwei; Bloom, Jason; Noaman, Samer; Chan, William
Abstract: Objectives: To conduct a systematic review and meta‐analysis of studies examining the impact of periprocedural intravenous morphine on clinical outcomes in patients undergoing primary percutaneous coronary intervention (PCI) for ST‐elevation myocardial infarction (STEMI). Background: Morphine analgesia may reduce the absorption of co‐prescribed P2Y12 antagonists attenuating platelet inhibition. The impact of periprocedural intravenous morphine on clinical outcomes in patients undergoing PCI for STEMI is not well defined. Methods: Analysis of the electronic databases of MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL), Scopus, Web of Science and ClinicalTrials.gov for association of peri‐PCI intravenous morphine use with in‐hospital or 30‐day myocardial infarction (MI) (primary outcome) and in‐hospital or 30‐day mortality. Results: A total of 11 studies were included for systematic review. One study was a randomized controlled trial, 10 were observational studies. Five studies including 3, 748 patients were included in meta‐analysis of in‐hospital or 30‐day MI. Within this group, patients were treated concurrently with ticagrelor ( n = 2, 239), clopidogrel ( n = 1, 256) and prasugrel ( n = 253). There was no significant association of in‐hospital or 30‐day MI with intravenous morphine (odds ratio 1.88; 95% confidence interval [CI] 0.87–4.09; I 2 0%). Across seven studies and 5, 800 patients, no increased risk of mortality at the same composite time endpoint was evident (odds ratio 0.70; 95% CI 0.40–1.23; I 2 19%). Conclusions: Periprocedural intravenous morphine administration was not associated with adverse short‐term clinical outcomes in patients undergoing primary PCI for STEMI. Further randomized trial data are needed to evaluate the pharmacologic interaction between morphine and P2Y12 antagonists with clinical outcomes.